A wish in the dark - Soontornvat, Christina (Somerville, Massachusetts : Candlewick Press, 2020)
All light in Chattana is created by one man--the Governor, who appeared after the Great Fire to bring peace and order to the city. For Pong, who was born in Namwon Prison, the magical lights represent freedom, and he dreams of the day he will be able to walk among them. But when Pong escapes from prison, he realizes that the world outside is no fairer than the one behind bars. Nok, the prison warden's perfect daughter, is bent on tracking Pong down and restoring her family's good name. But as Nok hunts Pong through the alleys and canals of Chattana, she uncovers secrets that make her question the truths she has always held dear.
School Library Journal, February 2020
Booklist starred, February 2020
Publishers Weekly, January 2020
Booklist, February 2020
Bulletin (Center for Children's Books), March 2020
Kirkus Review, February 2020
Keywords: Prisoners -- Juvenile fiction; Thailand -- Juvenile fiction; Prisoners -- Fiction; Thailand -- Fiction; Fantasy fiction